(untitled) (Relevant Tomorrow / Aktualu rytoj, 2025)
The article analyses the history of the interdepartmental institution of the Republic of Lithuania, the Genocide and Resistance Research Centre of Lithuania, focusing on its establishment, development, internal problems, and impact on the national culture of remembrance, particularly on memory of the Holocaust, while comparing it with similar institutions in other countries. The author of the article argues that the main source of tension within (and around) the Centre has stemmed from its ambiguous nature—the attempt to function both as an expert institution and a representative institution. The Centre’s primary focus on researching and commemorating the crimes and victims of the Soviet regime and the marginalization of the Holocaust theme in all activities, as well as its conservative approach to the complex issues of twentieth-century history are its key weaknesses and vulnerability to criticism.